Determinants of costs of care for patients attending primary care - Salokangas Henri; From Tiina; Luutonen Sinikka; Hietala Jarmo; Salokangas Raimo (Psykiatrian Tutkimussäätiö, 2022)
Aims: We aimed to evaluate determinants of costs of somatic and psychiatric care for
patients attending primary care (PrC).
Methods: 495 PrC patients filled in a questionnaire including questions on background,
health behaviour, social contacts, perceived health and depressive symptoms. Costs of
somatic and psychiatric care were obtained from the local healthcare register.
Results: During 5 years’ follow-up, total inflation-adjusted costs of care were 8145 Euros
per capita in 2010 prices: 87.2% was due to somatic and 12.8% to psychiatric care. Age
associated positively, but being single and working associated negatively with costs
of somatic care. Costs of psychiatric care were high in young adults, single,
divorced, unemployed, smokers, and those with few social contacts. In zero-inflated
multivariate modelling, poor perceived health and being retired increased probability
of seeking somatic care. Depressive symptoms and being unemployed increased, and old
age decreased probability of seeking psychiatric care.
Concerning both services together, poor perceived health and being retired associated
with increased, but depressive symptoms with decreased likelihood of being a service
user. Among service users, age group 25-44 and having poor perceived health associated
with higher costs of care. Female gender, being single, employed, having low education
level, regular user of alcohol and regular physical exercise associated with lower
costs of care.
Conclusions: In patients attending PrC, more than a tenth of total costs of care were
due to psychiatric care. Patients’ perceived health associated with costs of somatic,
and depressive symptoms with costs of psychiatric care. Sociodemographic background
also associated with costs of care.